Presentation Skills Assessment Tools - Leila Jahangiri; Thomas Mucciolo (Association of American Medical Colleges, 2010)
Abstract This resource is a collection of interactive assessment tools designed to measure presentation effectiveness by self-evaluation or by peer evaluation. The resource contains three evaluation forms, each of which takes less than 5 minutes to complete. The first is for standard lectures, presentations, or seminars, where the presenter is seen and has accompanying slides. The second is for speech-only lectures or speeches, where the presenter is seen but does not have accompanying slides. Finally, there is a form for webinars, where the presenter is only heard and has accompanying slides. As perceived by two different types of audiences, student learners and professional learners, it has been determined that there are 21 desired skill categories and that students and professionals value these categories differently. Therefore, each assessment tool summarizes the results (speaker index) of all skill categories and then calculates the index according to different types of learners (students, professionals, and both). In order to observe the usability and applicability of the tools across an even wider spectrum of diverse teaching methods, this resource has been offered and used with more than 1,280 individuals in diverse fields internationally. These interactive assessment tools are designed to be user friendly, to be non-labor intensive, and to provide immediate feedback and a measurable pathway to self-improvement in medical and dental education as well as in other professions. It is suggested that these forms be used with other evaluation methods. The feedback from these forms can assist with faculty development, improve general presentation/teaching skills, and provide input regarding online teaching. These forms are not limited to use in medicine and dentistry.